Dos consultórios sentimentais à rede : apoio emocional pelas mídias digitais - Prado, Juliana do (Universidade Federal de São Carlos, 2015)
The purpose of this research is to analyze the uses of digital media such as emotional support, conceptualized as a social relation in which people are looking for help to deal with emotional demands. These are referred initially to love relationships which lead to subjective processes that deal with gender, social class, sexuality, race, age, occupation, among other possible axes of analysis. The goal is to discuss what digital media settings have assumed about the search for emotional support, articulated the morals of their uses and subjective processes. Thus, the empirical field was constructed from three research fronts: the first analyzes speeches of sites that present emotional counseling through the mode I call as digital sentimental office; the second analyzes the professional use of new technologies by psychologists that provide therapeutic care over the Internet, setting the counseling and the third in which I analyze the online community uses, called networks. I intend to explore meanings and morals around digital media uses from discourses and practices of both people who use these media with these objectives, as the professionals who have joined the appeal of digital media to promote counseling. Throughout the work are presented discussions of these three fronts that constitute this research, in order to point some aspects that allow confronting the different search modes for emotional support by digital media in their speeches, uses and interests remain in the dispute for expertise in this area. The hypothesis is that has set up an emotional support market through digital media. However, differently to other media, the segmentation occurs concomitantly to the uses of people, allowing agencies and flows between platforms which can culminate into other forms of support. The proposal is addressing the elements of emotional support in each front in order to verify continuities and ruptures between what is conceptualized as support, especially pointing to morals and specific forms of subjectivity.
Keywords: Emotional support; Digital media; Moralities; Subjective processes; Segmentation; Apoio emocional; Mídias digitais; Moralidades; Processos de subjetivação; Segmentação; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA DA SAUDE